INFLUENCE OF THE NUMBER OF LAYERS AND THEIR ORIENTATION ON THE NATURAL FREQUENCIES OF COMPOSITE PLATES (Uzbekistan Open Conference, 2025)
This article examines the influence of the number of layers and the orientation angles of reinforcing fibers on the natural frequencies of multilayer composite plates. A theoretical analysis and numerical calculations were performed using finite element modeling methods and the Maple package. It was found that increasing the number of layers and choosing the right orientation significantly improves the flexural stiffness and natural frequencies of the structure. The results obtained can be applied to the design of lightweight and stable components in aviation and construction.